Impact Analysis of Public Transport on Traffic Congestion: Case Study of Jalan Pangeran Muhammad, Majalengka - Vickry Afrizal Herdiawan; Mohamad Taufik; Jody Martin Ginting (Fakultas Teknik Sipil dan Perencanaan, 2025)
Majalengka Regency is a Level II area experiencing rapid traffic growth. Impact analysis of public transportation on traffic congestion is needed to maintain the smooth running of existing traffic roads in Majalengka, especially in the Simpeureum area on Jalan Pangeran Muhammad, which is the main route with several schools, including SMPN 1 Cigasong, being one of the areas where traffic congestion occurs in West Java Province. This paper aims to impact analysis of public transportation on traffic congestion and determine what effects of public transportation can cause traffic congestion. Often, drivers of public transportation or for example public transportation that park their cars carelessly when dropping off passengers on the side of the road and do not see the surroundings, blocking other vehicles that want to pass behind them so that traffic jams occur even if only a fraction of a second. This problem has long been a core issue in Indonesia, especially in areas with high public transportation use. As well as analyze related issues in the discussion. The research method was carried out by survey for the research source located in Simpeureum, which is on Jalan Pangeran Muhammad, which will go to Rajagaluh - Cirebon road in January 2025 and for data analysis using quantitative. The results showed that the impact of public transportation on traffic congestion still affects traffic roads by parking their vehicles carelessly when dropping off passengers so that other drivers have to wait. However, the relatively short time significantly affects other drivers' time. This paper concludes that congestion caused by public transportation also significantly impacts other drivers. This usually happens because the high rate of indiscriminate parking when dropping off passengers is due to the lack of supporting facilities such as bus or public transportation stops.